Tauhid Ahlussunnah wal Jama’ah; Antara Imam al-Asyari dan Ibn Taymiyyah - Muhammad Imdad Rabbani (Tasfiyah: Jurnal Pemikiran Islam, 2019)
This paper wants to highlight the distinct problem in understanding monotheism. That is the understanding that came from Abu al-Hasan al-Asy'ari with Ibn Taimiyyah. The emphasis of the discussion is located on whether the difference between the two in understanding tauhid has entered the realm of ushul aqeedah or not? Because of this difference, one of the followers called the other one ‘out’ from ahl sunnah wa al-jama'ah. This problem is increasingly relevant to be discussed because both are often bumped into each other; as if it could not come together otherwise there is no point of equality. On the one side Asy'ari inherits a thick kalam tradition, while on the other hand Ibn Taimiyyah tends to be critical of this tradition. For the second group, the kalam tradition is called too rational and is considered dangerous to interpreting the issue of aqeedah. Therefore, this paper specifically wants to highlight some of the problems above, to a minimize of finding common ground while at the same time providing an alternative view that is often missed a lot of people